Pregnant Women's Reports of the Impact of COVID-19 on Pregnancy, Prenatal Care, and Infant Feeding Plans. Issue 1 (January 2021) - Burgess, Adriane; Breman, Rachel Blankstein; Bradley, Dani; Dada, Sophia; Burcher, Paul
Abstract: Purpose: The aim of this study is to describe how the COVID-19 (coronavirus) pandemic has affected pregnancy, prenatal maternity care practices, and infant feeding plans among pregnant persons in the United States. Study Design: Cross-sectional descriptive study using an app-based survey. Methods: A link to the survey was sent via email to users of the Ovia Pregnancy app on May 20, 2020 and was open for 1 week. Participants were asked to complete the survey as it applied to their pregnancy, breastfeeding, and maternity care received during the COVID-19 pandemic, beginning approximately February 2020 through the time of the survey. There were 258 respondents who completed the survey. Results: The majority (96.4%; n = 251) of pregnant women felt they received safe prenatal care during this time period. Slightly less 86.3% ( n = 215) felt they received adequate prenatal care during this time period. 14.2% ( n = 33) reported changing or considering changing the location where they planned to give birth due to COVID-19. Of those who reported they had begun purchasing items for their baby, 52.7% reported that the COVID-19 pandemic has affected their ability to get items they need for their baby. Clinical Implications: Although it is imperative to implement policies that reduce risk of transmission of COVID-19 to pregnant women and health care providers, it is necessary for health care providers and policy makers to listen to the collective voices of women during pregnancy about how COVID-19 has affected their birth and infant feeding plans and their perception of changes in prenatal care. Abstract : The COVID-19 pandemic has had a major impact on all aspects of health care including prenatal care, childbirth, and infant feeding. In this research, an interdisciplinary group of clinicians surveyed pregnant women across the United States using a pregnancy app to see how the pandemic has affected them during the childbirth process. The voices of these new mothers are highlighted in this study.